A New Report of Combined Central and Peripheral Demyelination: A Case Report - Alshamrani, Foziah; Alyami, Rawan; Alghanimi, Ibrahim; Alajaji, Reef; Alkhaldi, Modhi; Alamri, Abdulla (Frontiers in Neurology, 2021)
Combined central and peripheral demyelination (CCPD) is not encountered frequently in the clinical practice and it requires a high level of suspicion for diagnosis. We describe a case of a young man who was diagnosed with multiple sclerosis (MS) after presenting initially with symptoms suggestive of central nervous system (CNS) insult in form of double vision, slurred speech, left-sided numbness, and unsteadiness. However, on the next day of admission his neurological examination was remarkable for ataxia, areflexia, and ophthalmoplegia the typical triad of Miller Fisher syndrome (MFS). After confirming both diagnoses, the final diagnosis of CCPD was made. The challenges one may face to diagnose and treat CCPD urge sharing of similar cases to open the door for further extensive and thorough investigations and to encourage further studies and analysis of available data to come up with consolidated management guideline for rare disorders.